Epilepsy and Hemi Paretic Cerebral Palsy - J Gordon Millichap (Pediatric Neurology Briefs)
The incidence of epilepsy, the IQ, and laterality of cerebral palsy were investigated in 51 children with hemiparetic CP at the Department of Neurology, Charles University, Katerinska, Praha, Czechoslovakia.